Clinical Outcomes of Limited Open Intramedullary Headless Screw Fixation of Metacarpal Fractures in 91 Consecutive Patients - Eisenberg, Gilad (Hand (N Y), 2019)
Background: The objective of the study is to evaluate clinical and radiographic outcomes in patients treated with limited-open retrograde intramedullary headless screw (IMHS) fixation for metacarpal neck and shaft fractures. Methods: Retrospective review of 91 consecutive patients (79 men; 12 women), mean age 28 (range =15-69) years, treated with IMHS fixation for acute displaced metacarpal neck (N = 56) and shaft (N = 35) fractures at a single institution. Mean follow-up was 10 (range = 1-71, median = 3) months. Preoperative mean magnitude of metacarpal neck angulation was 48° (range = 0°-90°), and mean shaft angulation was 42° (range = 0°-70°). Active motion was initiated within 5 days postoperatively. Clinical outcomes were assessed with digital goniometry, grip strength, and return to full activity. The time to radiographic union and radiographic arthrosis was assessed. Results: All 91 patients achieved full functional arc of metacarpophalangeal (MCP) motion, and all achieved full active MCP extension or hyperextension. At mean follow-up of 10 months, postoperative mean MCP joint flexion-extension arc was 88° (range = 55°-110°). Grip strength was available for 52 patients and measured 104.1% of the contralateral hand (range = 58%-230%). Radiographic union data were available for 86 patients. Seventy-six percent (65/86) achieved radiographic union by the end of week 6 (range = 2-10 weeks). Early arthrosis was noted in 1 patient at the MCP. There were 3 cases of shaft refracture after recurrent blunt trauma, following prior evidence of full osseous union. Conclusions: The IMHS fixation is safe, reliable, and durable for metacarpal neck/subcapital, axially stable shaft fractures, and select delayed unions or malunions. It allows for early postoperative motion without affecting union rates and obviates immobilization. This technique offers distinct advantages over formal open reduction and percutaneous Kirschner wire techniques.